BIOTECHNOLOGICAL POTENTIAL OF SOYBEAN PLANT GROWTH-PROMOTING RHIZOBACTERIA - Paula, Gabriel Ferreira de (2021)
Technologies that use rhizobacteria to promote plant growth are increasing in agriculture, results have shown improvements in soil quality, increases in productivity, and decreases in the use of synthetic inputs, The objective of work was to characterize bacterial isolates regarding their biological activity and growth promotion of soybean plants grown in a controlled environment. Fifteen bacteria were isolated from soils with continuous use of biological fertilizer. They were evaluated for enzymes production (amylase and protease), nitrogen fixation, antagonistic activity to phytopathogenic fungi, and indoleacetic acid (IAA) production, Soybean seeds were inoculated with bacterial isolates in a greenhouse and evaluated for plant development and soil chemical attributes. The results showed that 8 of the 15 isolates presented production of amylase, protease, or both and 4 isolates presented nitrogen-fixing capacity. The percentage of isolates with high or moderate inhibitory action against the fungi Sclerotinia sclerotiorum, Macrophomina phaseolina, and Fusarium solani were 73.3%, 66.6%, and 73.3%, respectively. The IAA production varied from 8.56 to 31.33 µg mL-1 (5 isolates had low, 6 had moderate, and 4 had high production). The soybean development was significantly higher in 80% of the treatments with inoculation with bacterial isolates. Five bacterial isolates effectively present all characteristics for use as inoculant (biofertilizer) to promote the development of soybean plants.